Distance and Control in Don Quixote : A Study in Narrative Technique - El Saffar, Ruth S., 1941- (University of North Carolina publications of the Department of Romance Languages., 2019)
Ruth el Saffar's study of novelistic technique in Don Quixote focuses on the interplay of characters, authors, and readers who populate the work.